2016
DOI: 10.1111/ejss.12327
|View full text |Cite
|
Sign up to set email alerts
|

Changes in organic carbon and nitrogen in soil with metal pollution by Cd, Cu, Pb and Zn: a meta‐analysis

Abstract: Summary Organic carbon (OC) and nitrogen (N) storage in soil plays an important role in global climate change and in maintaining food security. Pollution of soil with heavy metals has occurred in many parts of the world, but their effects on soil OC and N have not been well addressed. Relevant data were extracted from peer‐reviewed journal papers and analysed by a meta‐analysis to determine how long‐term heavy metal pollution affected soil OC and N status. Plant biomass decreased significantly because heavy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Consequently, metal pollution decreased the amounts of available C and N released from the decomposition of large POM size fractions and then decreased C and N adsorption by clay minerals, resulting in smaller relative increases in OC and TN concentrations of organic-mineral compounds in polluted soils than control soils. In a meta-analysis study, Zhou et al (2016) reported that C/N ratios in bulk soils were higher after long-term metal pollution than controls. According to the results of Zhou et al (2016), higher C/N ratios in 2000e250 mm POM size fractions might be explained not only by the inhibitory effects of metals on OM decomposition taking the large POM size fractions closer to the original OM inputs with high C/N ratios but also by decreased plant N utilization efficiency, resulting in larger mineral N losses from polluted soils.…”
Section: Characteristics Of Oc Tn and C/n Ratio In Pom Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, metal pollution decreased the amounts of available C and N released from the decomposition of large POM size fractions and then decreased C and N adsorption by clay minerals, resulting in smaller relative increases in OC and TN concentrations of organic-mineral compounds in polluted soils than control soils. In a meta-analysis study, Zhou et al (2016) reported that C/N ratios in bulk soils were higher after long-term metal pollution than controls. According to the results of Zhou et al (2016), higher C/N ratios in 2000e250 mm POM size fractions might be explained not only by the inhibitory effects of metals on OM decomposition taking the large POM size fractions closer to the original OM inputs with high C/N ratios but also by decreased plant N utilization efficiency, resulting in larger mineral N losses from polluted soils.…”
Section: Characteristics Of Oc Tn and C/n Ratio In Pom Fractionsmentioning
confidence: 99%
“…The quantity and quality of SOM are important in the management of soil fertility, nutrient supply and carbon dynamics (Paul, 2016), and SOM quantity and quality can change in long-term metal polluted soils (Viventsova et al, 2005;Zhou et al, 2016). Particulate organic matter (POM) is the part of SOM that can be physically size-fractionated into different labile pools in water and used as an index of labile SOM status (Balesdent, 1996;Benbi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As the succession of the gut community has been shown to vary with age and stress, this could account for the decreased abundance of G. apicola in the foragers during almond pollination, which may be contributing to a dysbiotic gut community [63]. Within a colony, foragers interact with different plant species and individuals and may contact different floral chemicals that likely affect their gut microbiome [64]. Given the degree of variation in microbiome structure within a colony, we do not recommend that researchers pool honey bee guts for microbial analyses and instead separately sequence and analyze multiple individual bees from colony replicates.…”
Section: Microbial Diversity Between and Within Coloniesmentioning
confidence: 99%
“…mining, smelting, agriculture, waste disposal) is an environmental problem worldwide (COM, 2006;FAO and ITPS, 2015;He et al, 2015). Metals exert toxic effects on soil living organisms (van Straalen, 2004;Stankovic et al, 2014), affecting the sustainability of terrestrial ecosystems and, in some cases, human health (Naveed et al, 2014;Zhou et al, 2016;Morgado et al, 2017). Toxicity is known to be related to the metal fraction that can be taken up by organisms and subsequently interact with biological targets (i.e.…”
Section: Introductionmentioning
confidence: 99%